1972
DOI: 10.1037/h0032991
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned suppression of distress calls in imprinted ducklings.

Abstract: Newly hatched ducklings were exposed to imprinting procedures and their subsequent filial reactions were studied using a classical conditioning paradigm. The first experiment revealed that a previously neutral stimulus can become a conditioned suppressor of distress calling as a consequence of pairing it with the imprinted stimulus. If the presentation of the imprinted stimulus was, however, omitted or delayed, or if it preceded rather than followed the presentation of the neutral stimulus, the effect was not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1973
1973
1980
1980

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…It is noteworthy that similar operant responses have been taught to infant monkeys utilizing exposure to the mother surrogate as the reinforcing event (Harlow, 1958). In addition, Hoffman, Barrett, Ratner, and Singer (1972) have shown that the ability of an imprinting stimulus to suppress a duckling's distress calls can be classically conditioned to initially neutral environmental stimuli.…”
Section: Reinforcing Properties Of Eliciting Stimulationmentioning
confidence: 99%
“…It is noteworthy that similar operant responses have been taught to infant monkeys utilizing exposure to the mother surrogate as the reinforcing event (Harlow, 1958). In addition, Hoffman, Barrett, Ratner, and Singer (1972) have shown that the ability of an imprinting stimulus to suppress a duckling's distress calls can be classically conditioned to initially neutral environmental stimuli.…”
Section: Reinforcing Properties Of Eliciting Stimulationmentioning
confidence: 99%
“…Zajonc familiar stimulus, reduces distress calling (Zajonc,Markus,& Wilson 2) even when the prior exposure to the stimulus occurred prenatally (Rajecki, 1972). In a series of studies, Hoffman (Hoffman, Barrett, Ratner,& Singer, 1972;Hoffman, Eiserer, & Singer, 1972;Hoffman, Ratner,& Eiserer, 1972) employed the distress calling of ducklings to investigate, among other things, the changes in behavioral control exerted by different stimuli and differing amounts of experience with those stimuli. In all these studies, vocalization behaviors are taken as an index of attachment to the familiar.…”
Section: Introductionmentioning
confidence: 99%